2018
DOI: 10.1136/emermed-2017-207107
|View full text |Cite
|
Sign up to set email alerts
|

Understanding better how emergency doctors work. Analysis of distribution of time and activities of emergency doctors: a systematic review and critical appraisal of time and motion studies

Abstract: The review revealed that senior doctors spent a large percentage of their time on direct face-to-face contact with patients. The review findings provided a grounded understanding of how senior doctors spent their time in the ED and could be useful in implementing improvements to the emergency care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
4
9
0
2
Order By: Relevance
“…Therefore, it has been proposed that multitasking is a key ability of ED providers [3,[13][14][15]. Although ED physicians frequently operate under a barrage of multiple and competing demands, the very consequences of multitasking for provider outcomes are not well understood [3,10,11,16]. Particularly the following questions remain unresolved:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it has been proposed that multitasking is a key ability of ED providers [3,[13][14][15]. Although ED physicians frequently operate under a barrage of multiple and competing demands, the very consequences of multitasking for provider outcomes are not well understood [3,10,11,16]. Particularly the following questions remain unresolved:…”
Section: Introductionmentioning
confidence: 99%
“…First, there is a paucity of naturalistic studies on multitasking demands in acute care settings with real observational data that closely approximate ED conditions under which multitasking takes place [10,16,17]. Secondly, a thorough understanding concerning multitasking and its consequences for provider outcomes such as work stress and cognition is needed [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bedeutsame Anteile werden für Kommunikation, Dokumentation und administrative Aufgaben aufgebracht. Diese Zeitanteile variieren stark für einzelne Tätigkeiten [6].…”
Section: Hintergrund Und Fragestellungunclassified
“…Daher ist die Bestimmung berufsgruppenspezifischer Unterschiede und Gemeinsamkeiten essenziell, um eine gesamtheitliche Beurteilung der Zeitverteilung beider Professionen zu gewähren [8,9]. Von trainierten Expert*innen durchgeführte systematische Beobachtungsstudien ("timemotion studies") sind ein zuverlässiger Weg, Art und Dauer von Aktivitäten der Beschäftigten in der klinischen Akutund Notfallmedizin zu erfassen [6,10].…”
Section: Hintergrund Und Fragestellungunclassified
“…In the ED, we make myriad decisions each shift, as described in Michieletto's article in this issue of Emergency Medicine Australasia. 3,4 However, not only is there a large volume of decisions being made, the nature of these decisions is also different to other areas of medicine, with multi-tasking a common feature of emergency work, resulting in 77 min of overlapping activity performed each hour. 5 As emergency clinicians, interruptions are often necessary given the nature of our work environment; however, these disruptions to our train of thought add upone study found the average number of interruptions to emergency clinicians was 9.7 per hour, compared with 3.9 per hour in primary care colleagues.…”
mentioning
confidence: 99%